ORIGINAL ARTICLE: Membrane Stabilizing Activity and Protein Denaturation: A Possible Mechanism of Action for the Anti-Inflammatory Activity of Phyllanthus amarus - Atul R. Chopade; Prakash M. Somade; Fahim J. Sayyad (Journal of Krishna Institute of Medical Sciences University, 2012)
Background: Previous studies confirm the anti-inflammatory potential of Phyllanthus amarus herb. Aim and objective: Primary aim of the present study was to investigate the possible anti-inflammatory mechanism of Phyllanthus amarus extract using in-vitro models. Material & method: Aqueous extract of Phyllanthus amarus was evaluated in vitro models for haemolysis of erythrocytes and % inhibition in heat induced protein denaturation at three doses 50 mg/kg, 100 mg/kg & 200 mg/kg. Results: The aqueous extract of Phyllanthus amarus significantly inhibited the haemolysis of erythrocytes and heat induced protein denaturation as compared to control. Conclusion: It can be postulated from the observed results that the anti-inflammatory activity of Phyllanthus amarus could be due to its membrane stabilizing action and inhibition of protein denaturation.